Penggunaan Statistik Nonparametrik Dalam Menentukan Determinan Keputusan Konsumen Dalam Membeli dan Mengkonsumsi Berbagai Merek Susu Kemasan: Ditinjau dari Perspektif Popularitas, Kualitas dan Harga - Kharisma, Bayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.04.TAHUN 2018, 2018)
This study aims to analyze consumer perceptions of the popularity, quality and price of various brands of milk and determine the determinants of consumer decisions in buying and consuming various brands of packaging milk from the perspective of popularity, quality and price. The methodology used in this research is nonparametric statistics with respondents consisting of middle to upper income class, the selection of upper middle class is based on the consideration that dairy products in the packaging including quite expensive. The result of research shows that there are 41 brands of milk that the respondents choice with the popularity level, that is: (1) Dancow with the number of respondents 72 (52,94%); (2) Flag with number of respondents 44 (32,59%); (3) Indomilk with 36 respondents (26,86%); (4) Sustagen HP with the number of respondents 18 (14.40%) and Anlene with the number of respondents 21 (17.95%) Most respondents chose Dancow milk caused by several things, such as quality content of nutrient content levels and vitamins and the level of consumer confidence in the cleanliness and originality of the content from the process until distribution plus the guarantee from Nestle producers that have been famous all over the world with quality and quality assurance, plus the respondents data about the selection of quality milk showed that 52 respondents (38.52%) states that Dancow milk has the best quality among the others.